Teaching integrated language skills - Herrera Guillen, Paula Yanet (2018)
The present monograph refers to Teaching Integrated Language Skills, which will show us the importance of developing the four language skills using techniques to help students the successful achievement in their language learning, to integrate the four language skills more effectively and to create more opportunities to practice the language in the real context.